The Scottish Referendum. Issue 2 (May 2016) - Emerson, Peter
Abstract : And the winner was… devo-max. It was not on the ballot paper; it received just a handful of spoiled votes; but it won. So maybe the two-option, yes-or-no ballot was not the most appropriate decision-making methodology. Rather, a three-option poll might have been the catalyst for a more subtle debate and a more accurate outcome, while a preferential vote on five or six options could have catered for even more sophistication. Accordingly, this article questions the decision to restrict the 2014 referendum to two options. Next, it asks what might have happened if a three-option ballot had been held. It then compares what could happen under different voting procedures before advocating a more inclusive structure. And lastly, consideration is given to multi-option referendums, both in Scotland and abroad.